Union Renewal in Chile and the Rate of Surplus Value: A Marxist Approach - Gonzalo Durán; Michael Stanton (World Review of Political Economy)
In Chile during the period 2006–2016, workers’ organization and industrial insurgency grew, especially in the export sectors of the economy. The conventional approach has labeled this period as one of union renewal since rank-and-file organizations involved measures such as strikes and raised union density. This article raises the question of how exploitation could increase despite the presence of active rank-and-file movements during this period and investigates why union renewal is not accompanied by substantive improvements for the working class. This topic is of fundamental importance from a Marxist standpoint and adds more complexity to the understanding of the scope of union renewal in a particular country at a specific time.